Reelin Is a Serine Protease of the Extracellular Matrix - Quattrocchi, Carlo C.; Wannenes, Francesca; Persico, Antonio M.; Ciafré, Silvia Anna; D'Arcangelo, Gabriella; Farace, Maria G.; Keller, Flavio (The Journal of biological chemistry, 2002)
Reelin is an extracellular matrix protein that plays a pivotal role in development of the central nervous system. Reelin is also expressed in the adult brain, notably in the cerebral cortex, where it might play a role in synaptic plasticity. The mechanism of action of reelin at the molecular level has been the subject of several hypotheses. Here we show that reelin is a serine protease and that proteolytic activity is relevant to its function, since (i) Reelin expression in HEK 293T cells impairs their ability to adhere to fibronectin-coated surfaces, and adhesion to fibronectin is restored by micromolar concentrations of diisopropyl phosphorofluoridate, a serine hydrolase inhibitor; (ii) purified Reelin binds FP-Peg-biotin, a trap probe which irreversibly binds to serine residues located in active catalytic sites of serine hydrolases; (iii) purified Reelin rapidly degrades fibronectin and laminin, while collagen IV is degraded at a much slower rate; fibronectin degradation is inhibited by inhibitors of serine proteases, and by monoclonal antibody CR-50, an antibody known to block the function of Reelin bothin vitro and in vivo. The proteolytic activity of Reelin on adhesion molecules of the extracellular matrix and/or receptors on neurons may explain how Reelin regulates neuronal migration and synaptic plasticity.